Analisis Kesulitan Guru dan Siswa pada Materi Statistika di SMA Advent Purwodadi - Suliani, Mega; Saputri, Rinda Azmi (Mandalika Mathematics and Educations Journal, 2021)
This study aims to analyze the difficulties experienced by students and teachers, especially in statistical materials and offered alternative solutions. The method used in this study used a qualitative approach with a descriptive type. The subjects in this study were 32 students of class XI IPA and a mathematics teacher at SMA ADVENT Purwodadi Malang. The results showed that the teacher had difficulty explaining the statistical material in group data. The difficulties faced by the teacher were caused by students who had difficulty in applying the group data formula. The difficulties faced by students vary, including understanding concepts (misconceptions), formulation (error in principle), modeling (fact errors), and calculation operations (operating errors). The difficulties experienced by the students resulted in the difficulty level of the questions. The problems given fall into the medium and easy criteria. An alternative solution is offered, that is, when learning for statistics material, it can use a problem-based learning model.AbstrakPenelitian ini bertujuan untuk menganalisis kesulitan yang dialami peserta didik dan guru khususnya pada materi statistika serta solusi alternative yang ditawarkan. Metode yang digunakan dalam penelitian ini menggunakan pendekatan kualitatif dengan jenis deskriptif. Subjek dalam penelitian ini yaitu Peserta didik kelas XI IPA dengan jumlah 32 peserta didik dan seorang guru matematika di SMA ADVENT Purwodadi Malang. Hasil Penelitian menunjukan bahwa guru mengalami kesulitan saat menjelaskan materi statistika pada data kelompok. Kesulitan yang dihadapi guru disebabkan oleh peserta didik yang kesulitan pada penerapan rumus data kelompok. Kesulitan yang dihadapi Peserta didik beragam diantaranya pemahaman konsep (kesalahan konsep), perumusan (kesalahan prinsip), pemodelan (kesalahan fakta), serta oprasi hitung (kesalahan operasi). Kesulitan yang dialami oleh perseta didik berakibatkan pada tingkat kesukaran soal. Persoalan yang diberikan masuk pada kriteria sedang dan mudah. Solusi alternative yang ditawarkan yaitu pada saat pembelajaran untuk materi statistika dapat menggunaan model pembelajaran berbasis masalah